2015
DOI: 10.3171/2014.12.jns14185
|View full text |Cite
|
Sign up to set email alerts
|

The association between expansive arterial remodeling detected by high-resolution MRI in carotid artery stenosis and clinical presentation

Abstract: OBJECT The purpose of the present study was to investigate the association between carotid artery (CA) expansive remodeling (ER) and symptoms of cerebral ischemia. METHODS One hundred twenty-two consecutive CAs scheduled for CA endarterectomy (CEA) or CA stent placement (CAS) were retrospectively studied. After excluding 22 CAs (2 were contraindicated for MRI, 8 had near-occlusion, 6 had poor image quality, and 6 had restenosis after CEA or CAS), there were 100 CAs (100 patients) included in the final analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…ERR was calculated from the long-axis MRI T1-weighted plaque image according to the method described by Yoshida et al [10]. ERR was defined as the ratio of the maximum distance between the inner border of the arterial lumen and outer borders of the plaque to the maximal outside diameter of the internal carotid artery distal to the plaque ( Fig.…”
Section: Measurement Of Expansive Remodeling Ratementioning
confidence: 99%
See 1 more Smart Citation
“…ERR was calculated from the long-axis MRI T1-weighted plaque image according to the method described by Yoshida et al [10]. ERR was defined as the ratio of the maximum distance between the inner border of the arterial lumen and outer borders of the plaque to the maximal outside diameter of the internal carotid artery distal to the plaque ( Fig.…”
Section: Measurement Of Expansive Remodeling Ratementioning
confidence: 99%
“…A promising approach would be to establish a logical stratification scheme to improve risk assessment for ischemic complications. Recent studies suggest that expansive arterial remodeling is related to plaque vulnerability [9,10]. Based on these findings, we tested the hypothesis that expansive arterial remodeling is a predictor of ischemic complications following CAS.…”
Section: Introductionmentioning
confidence: 96%
“…A high value was defined as 2 standard deviations (1.66) or more of the mean control ERR (1.36), which was calculated from normal carotid arteries without stenosis in our previous study. 34 In the same previous study, the mean ERR of patients with carotid stenosis was 1.68 ± 0.40, and the receiver-operating characteristic analysis found that when the cutoff value of ERR was set at 1.88, the sensitivity and specificity for the detection of ischemic symptom were 0.6 and 0.78, respectively. If the cutoff value of ERR was set at 1.88 in the present study, the number of patients with ischemic events within 6 months was also significantly higher in Group A (rSI ≥ 1.4 and ERR ≥ 1.88) than in Group D (rSI < 1.4 and ERR < 1.88; p = 0.01).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…18 The ERR was calculated using long-axis BB-MRI and the following formula ( In our previous study about the ERR, the control ERR measured in the contralateral nonatherosclerotic ICA in patients with unilateral carotid artery stenosis was reported. 34 The control ERR (mean ± SD) was 1.36 ± 0.15. Two SDs of the mean control ERR, 1.66 or more, was defined as high ERR.…”
Section: Expansive Remodeling Ratiomentioning
confidence: 99%
See 1 more Smart Citation